Identifying information security opinion leaders in organizations: Insights from the theory of social power bases and social network analysis. Issue 112 (January 2022) - Dang-Pham, Duy; Kautz, Karlheinz; Hoang, Ai-Phuong; Pittayachawan, Siddhi
Abstract: Organizations are increasingly prioritizing the management of information security (InfoSec) to facilitate their data-driven business. There are densely connected organizational networks in modern organizations, where both formal and informal leaders influence other employees' InfoSec behaviors. We analyzed the organizational networks in a large organization and investigated the interactions that made employees appear as influential InfoSec opinion leaders to their colleagues. The findings indicate that influential InfoSec opinion leaders were perceived by colleagues as knowledgeable in InfoSec and capable of rewarding and sanctioning InfoSec behaviors. Other traits such as formal seniority, age, tenure, and department membership were also found to increase InfoSec leadership.